'All sorts of wonderful impossibilities': Tracing the Genesis of John McGahern's 'Doorways'. Issue 2 (November 2021) - Fox, Brian
Abstract : It is well known by now that John McGahern was a scrupulous reviser of his own work, even if this insight into his compositional methods has not been accompanied by a substantial body of research on the archive and the revisions themselves. This essay aims to address this anomaly by focusing on the genetic evolution of McGahern's short story 'Doorways'. Specifically, it will concentrate on the earliest handwritten drafts when the work is at its most provisional. The consensus view of McGahern's writing practices is of an artist committed to ideals of Flaubertian perfectionism, but implicit in this view is a bias towards the more granular work of late-stage refinement. The approach this essay takes shows McGahern at his most distant from the Flaubertian perfectionist that he is best known as, thus opening up new ways to reconsider how those works achieve their distinctive appearance of refined delicacy and simplicity.